STEM CELL THERAPY IN STROKE - Ahda, Yuni; Razak, Abdul; Zalni, Tita Yunia (Stem Cell Research and Development Center, Universitas Airlangga, 2023)
Stem cells are emerging as an attractive option because of their intrinsic ability as vectors for drug delivery to diseased tissues. The term stem cells or stem cells was first introduced by a Russian histologist, Alexander Maksimov (1874-1928). The purpose of this study is to describe the research and development of stem cell applications for stroke. This study is a literature study (review article) regarding stem cells (stem cells) in stroke which has been discussed in several scientific journals. From several articles that have been collected in giving stem cells to people with stroke, namely in bone marrow. MSC (Mesenchymal Stem Cell) is a multipotent stem cell from bone marrow and Adult SPM and because of its high applicability. Bone marrow is a rich source of hematopoietic stem cells so it can be applied to stroke patients.